2013
DOI: 10.1124/jpet.112.199489
|View full text |Cite
|
Sign up to set email alerts
|

The Antinociceptive Effect of Milnacipran in the Monosodium Iodoacetate Model of Osteoarthritis Pain and Its Relation to Changes in Descending Inhibition

Abstract: Osteoarthritis (OA) is a chronic joint disorder whose principal symptom is chronic pain. Current analgesics are inadequate and the mechanisms contributing to this pain are poorly understood but likely to include both local joint changes and central consequences. These studies used monoamine receptor agents combined with behavioral studies and single-unit dorsal horn recordings to examine whether descending noradrenergic and serotonergic inhibitions are altered in the monosodium iodoacetate model of OA pain, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 53 publications
7
17
0
Order By: Relevance
“…These observations are consistent with other studies reporting signs of neuropathic pain during the late phase of MIA-induced osteoarthritis 5, 17, 38 . Several studies demonstrated that MIA-induced late phase hypersensitivity and weight asymmetry are resistant to anti-inflammatory drugs (e.g.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These observations are consistent with other studies reporting signs of neuropathic pain during the late phase of MIA-induced osteoarthritis 5, 17, 38 . Several studies demonstrated that MIA-induced late phase hypersensitivity and weight asymmetry are resistant to anti-inflammatory drugs (e.g.…”
Section: Discussionsupporting
confidence: 93%
“…gabapentin, pregabalin) and reuptake inhibitors (e.g. amitryptaline, and milnacipran) are effective 5, 17, 38 . Notably, the concentration of MIA used in these studies (2 mg/25 μl corresponding to 80 mg/ml MIA) is the same as that used in our studies (4.8 mg/60 μl corresponding to 80 mg/ml).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a clinical study using fMRI identified an abnormal descending facilitatory system from the PAG to the spinal cord in patients with hip OA and descriptions of neuropathic pain (Gwilym et al 2009). An adaptive descending system has also been identified in the MIA model (Rahman et al 2009;Burnham and Dickenson 2013). First, a 5-HT 3 receptor antagonist inhibited evoked responses to innocuous stimuli yet did not produce this effect in controls, indicating an alteration in the facilitatory serotonergic system acting at 5-HT 3 receptors in the spinal cord was modulating low threshold neuronal responses akin to that seen after neuropathy (Rahman et al 2009).…”
Section: Changes In Descending Controls In Osteoarthritismentioning
confidence: 95%
“…As described earlier, rodent models of osteoarthritis can share common features with neuropathy resulting from peripheral nerve damage, for example, concurrent time‐dependent increases in descending facilitatory drive and loss of descending noradrenergic inhibition (Rahman et al, ; Burnham and Dickenson, ). Hence, the effects of TROX‐1 were additionally examined in the rat intra‐articular iodoacetate model of osteoarthritis, where treatment with TROX‐1 reversed behavioural hypersensitivity and weight‐bearing behaviour (Abbadie et al, ).…”
Section: Targeting α1 Vgcc Subunitsmentioning
confidence: 98%